Synthesis, Characterization and Bioactivity of New Phosphorous Containing Schiff Bases Prepared from Dithiocarbazate Derivatives and their Transition Metal Complexes - T. Al-Karkhi, Isam Hussain (2011)
Twelve novel phosphorous containing Schiff bases derived from the four isomeric dithiocarbazates which are methyl hydrazinecrabodithioate (SMDTC), phenyl hydrazinecarbodithioate (SBDTC), 2-methylbenzyl hydrazinecarbodithioate (S2MBDTC) and 4-methylbenzyl hydrazinecarbodithioate (S4MBDTC) with 2-(diphenylphosphino) benzaldehyde (DPPB), (triphenylphosphanylidene) acetaldehyde (TPPA) and (triphenylphosphanylidene)propan-2-one (TPPP). Metal complexes of Cd(II), Co(III), Cu(II), Ni(II) and Zn(II) were synthesized from these twelve Schiff bases to obtain sixty metal complexes. All these novel compounds have been successfully synthesized and characterized by various physico-chemical and spectroscopic techniques. The structures of nine Schiff bases and two transition metal complexes were successfully determined via X-ray crystallographic analysis. Four novel Schiff bases were coordinated in their metal complexes through nitrogen, sulfur and phosphorous donor atoms (PNS tridentate ligands), while the other eight Schiff bases coordinated through nitrogen and sulfur donor atoms (NS bidentate ligands). The cobalt complexes Co(SMDPB)2 NO3. 3H2O had distorted octahedral geometry, coordinating via the triphenylphosphine phosphorous, azomethine nitrogen and thiolate sulphur atoms of the Schiff bases. The nickel complex has square planar geometry and coordinated via azomethine nitrogen and thiolate sulphur atoms of the Schiff base, while the λ5 phosphorous do not coordinate. All the seventy two novel compounds have been evaluated for their biological activities against certain pathogenic microbial and two breast cancer cell lines, MCF-7 (human breast carcinoma cells with positive estrogen receptor) and MDA-MB231 (human breast carcinoma cells with negative estrogen receptor). The complexes were mostly antibacterial, but were less active against the fungal strains tested. The Schiff bases in this study show a weak activity except for S2MBDTPA which shows a moderate activity. Complexation of these Schiff bases with the transition metal ions will enhance and increased the activity significantly. It was also found that the complexes contain λ5 P shows more activity than λ3 P. The complexes were generally more active against the MCF-7 cell line as compared to the MDA-MB231 cell line. Most of the metal complexes exhibited higher bioactivity compared to their ligands in the complexes.